2010
DOI: 10.1007/s00467-010-1624-9
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular disease in children and adolescents with type 1 diabetes and obesity

Abstract: The incidence of type 1 diabetes (T1D) is increasing worldwide and is associated with a significant burden, mainly related to the development of vascular complications. Over the last decades, concomitant with the epidemic of childhood obesity, there has been an increasing number of cases of type 2 diabetes (T2D) among children and adolescents. Microvascular complications of diabetes, which include nephropathy, retinopathy and neuropathy, are characterized by damage to the microvasculature of the kidney, retina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 83 publications
1
47
2
1
Order By: Relevance
“…Supporting this premise, the present investigation identifies two vascular beds that are highly sensitive to impaired glucose control. Although the observed functional changes do not overtly perturb systemic hemodynamics or cerebral perfusion, they should not be underestimated: microvascular complications in diabetes are often asymptomatic during their early stages; once symptoms develop, they are generally difficult to reverse or clinically manage (32)(33)(34). Consequently, silent or asymptomatic microcirculatory dysfunction is now viewed as a key intervention point that can potentially alter the patient's clinical course.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this premise, the present investigation identifies two vascular beds that are highly sensitive to impaired glucose control. Although the observed functional changes do not overtly perturb systemic hemodynamics or cerebral perfusion, they should not be underestimated: microvascular complications in diabetes are often asymptomatic during their early stages; once symptoms develop, they are generally difficult to reverse or clinically manage (32)(33)(34). Consequently, silent or asymptomatic microcirculatory dysfunction is now viewed as a key intervention point that can potentially alter the patient's clinical course.…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate metabolic control directly correlated with kidney hyperfiltration and hyperperfusion. It presents one of the major risk factors for occurrence of AER among children and youth with DMT1 (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…High levels of HbA1C as a marker of chronic hyperglycemia are the most commonly determined risk factor for appearance of AER and development of DN in children and youth with DMT1 (16). Elevated values of systolic and diastolic blood pressure, according to some authors, appear independently from AER (16,17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has indicated that, with each 1 microgram per deciliter increase in blood lead level, children demonstrate decreasing performance on intelligence tests. (p. 23) Historically, African Americans have experienced and do experience racism. The impact of both overt and covert racism on African Americans has been well documented in literature.…”
Section: Racial Politics and Health Disparitymentioning
confidence: 99%
“…There is a valid basis for advocating positive, health-related choices that can change the prevalence rate of certain morbid conditions in varying populations. For example, teaching adolescents how to incorporate regular physical activities as a weekly routine may result in a corresponding decrease in the prevalence rate of obesity, and consequently reduce the risks of diabetes mellitus [23].…”
Section: Racial Politics and Health Disparitymentioning
confidence: 99%